Analisis Perbandingan Format Pesan ISO 8583 dan JSON pada Sistem Transaksi Keuangan - Suhanda Saputra (Bulletin of Computer Science Research, 2025)
The rapid development of financial transaction systems requires data exchange mechanisms that are fast, reliable, and easily integrable. ISO 8583 is a message format standard that has long been used in electronic payment systems such as ATMs, EDCs, and transaction switching networks, while JSON has been widely adopted in modern systems based on web services and microservices architectures. This study aims to analyze and compare ISO 8583 and JSON message formats in financial transaction systems in terms of data structure, message size efficiency, processing time, integration flexibility, and ease of system development and maintenance. The research method employs an experimental approach by simulating transaction transmission and processing using both message formats under identical transaction scenarios. The results indicate that ISO 8583 outperforms JSON in terms of message size efficiency and processing speed, making it more suitable for real-time transaction systems with high performance requirements. In contrast, JSON offers superior readability, flexibility, and ease of integration with modern systems, despite having higher data overhead. This study concludes that the selection of a message format should be aligned with system requirements, where ISO 8583 is more appropriate for core payment systems, while JSON is better suited for service integration and modern financial application development.